Analisis Reduplikasi Pada Film Sejuta Sayang Untuknya Karya Herwin Novianto - Nadya, Sarah; -, Istiqamah; Rahmah, Aulia; Aqlima, Siti (Jurnal Bahasa Indonesia Prima (BIP), 2024)
Reduplication techniques are often used in film production. This study aims to analyze the film Sejuta Sayang Untuknya by Herwin Novianto (a writer known for his finesse) to find out the form and meaning of repeated phrases. The research for this video uses a descriptive qualitative method. This research aims to dissect Herwin Novianto's Sejuta Sayang Untuknya movie to find out its reduplication structure. The listening method is used to collect data, followed by the note-taking technique, which documents the research data based on the listening results. The collected data allows us to classify the repeated words into four forms: for example, complete duplication of three data points, two partial duplications of three data points, three data points combined with thirteen affixes data, and four data points combined with one phoneme change data. The different forms of the repeated base word give rise to different meanings in the repeated words in the movie. Twenty types of repeated words were identified in Herwin Novianto's movie Sejuta Sayang Untuk Nila.